Determinants Quality of Life on People Living with HIV at the Regional General Hospital Of Kendari City - Nurmi, Wati; Rahmawati, Rahmawati; Sartini Risky (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: HIV/AIDS is known to have become an emergency problem throughout world, where infection transmission, morbidity and mortality rates are still high. At the Kendari City Hospital, in 2021 the HIV/AIDS IR was 75/100,000, in 2022 the HIV/AIDS IR was 183/100,000. Meanwhile, in 2023 the HIV/AIDS IR will be 206/100,000. This research aims to analyze the determinants of quality of life of PLHIV in the Kendari City Regional Hospital. Method: research is quantitative, using a cross sectional study research design. The population in study were HIV/AIDS sufferers who live in Kendari City and are undergoing treatment at the Kendari City Hospital in 2023, namely 316 people. The total research sample was 177 people, sampling used Simple Random Sampling. Data collection was carried out through observation and interviews using questionnaires and secondary sources through official Health Services and hospitals. Data analysis was carried out descriptively and inferentially using Chi Square test and logistic regression analysis. Results: shows that there is a relationship between nutritional status and the statistical value P Value X2 hit= 17.635 > X2 tab= 3.841, Sig value. 0.000 < α = 0.05 and Phi value = 0.328 and social support with statistical value P Value = X2 hit= 13.525 > X2 tab= 3.841, Sig value. 0.000 < α = 0.05 and Phi value = 0.288 with the quality of life of people with HIV/AIDS